Searching in Phenomenology Theory in Practice, Multisensory Approach of Architecture in Historical Places - Alawi Sayed Sadiq; Islam Hamdi Elghonaimy; Mahtab Asvar (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Heritage architecture, Beyond its historical, artistic or cultural value, embodies a profound symbolic significance, one that is intricately linked to the sensory experiences it evokes. Designing heritage areas must follow a unique way of dealing with the value of the heritage areas however,sensing the visitors is the target of designers while preparing their conspectus design. attracting the senses of users and having appropriate bodily experiences are major points in designing. Phenomenology in architecture, especially in heritage spaces, emphasizes the importance of a multisensory approach.In this context, architecture is a physical structure and a medium that conveys and mediates meanings through a rich tapestry of sensory experiences. This exploration will encompass various phenomena such as light, sound, smell, and texture, which are integral to creating atmospheres that define the experience – atmospheres of transcendence, eternity, community belonging, and an extraordinary spatial character. This paper aims to shift the perspective on how architecture should be approached, especially in conserving and protecting cultural heritage.